Treatment of Central Nervous System Manifestations of HIV in the Current Era - Handoko, Ryan; Spudich, Serena (Seminars in Neurology, 2019)
Treatment of neurological, neurocognitive, and neuropsychiatric impairment in the setting of human immunodeficiency virus (HIV) infection remains a complex problem, given several possible mechanisms of pathogenesis. The etiology must be determined based on clinical judgment and objective evidence, including cerebrospinal fluid (CSF) data from lumbar puncture and neuroimaging information from magnetic resonance imaging, when available and indicated. Other neuroinfectious etiologies must be ruled out, including central nervous system (CNS) opportunistic infections. HIV replication in the CNS (including CSF escape) should be evaluated for and excluded. If CSF HIV is detected, we recommend a treatment switch to antiretrovirals (ARVs) targeted to address any CSF HIV resistance mutations identified, or empiric treatment intensification using ARVs with high CNS penetration. If CSF HIV is not detected, treatment intensification with CCR5 inhibitors may be considered as an adjunct to reduce neuroinflammation. Finally, the current ARV regimen must be examined for possible neurotoxicity. Efavirenz has been well-recognized for its neuropsychiatric adverse effects and potential for causing sleep disturbances. Similar concerns have recently been raised with integrase inhibitors, especially dolutegravir and raltegravir, although further studies are needed to determine the risks for clinically relevant neuropsychiatric side effects from these medications, given their overall high potency and proven success in treating systemic HIV.
Keywords: central nervous system HIV; HIV comorbidities; chronic central nervous system infections; HIV-associated neurocognitive disorder; antiretroviral therapy